STIMULASI ORANG TUA DENGAN PERKEMBANGAN ANAK USIA TODDLER (1-3 TAHUN) DI DUSUN 02 RANGGON KABUPATEN KARAWANG 2023 - Desty Lismayanti; Intan Dini Adiyanti (Bajang Institute, 2024)
Parental stimulation for toddlers (1-3 years) is very important in following their development because it will determine the quality of health in the future. The developments monitored are gross motor, fine motor, speech and language skills, socialization and independence. Parental stimulation is part of the child's basic needs, namely sharpening. The purpose of this study was to determine the relationship between parental stimulation and the development of toddlers (1-3 years) in Dusun 02 Ranggon, Karawang Regency. The research design used in this study is a quantitative method with a cross sectional approach. The sample size that the researchers used was 96 respondents with a stratified random sampling technique. Analysis using the chi-square test obtained a P value of 0.012. This research is expected to be useful for parents to pay more attention to children's development and provide good stimulation so as to minimize disruption or developmental delays in toddler-aged children